Formulation of Microbial Consortium as an Inoculant for Agarwood Induction - Sabella, Justin (Universiti Malaysia Sarawak (UNIMAS), 2020)
Agarwood or gaharu is well known as the most valuable resinous heartwood that can reach up to US$100,000 per kilogram in market price due to its superior quality and high purity of materials. Agarwood has a high commercial value due to its fragrance properties and medicinal value. Agarwood commonly occur within the trees of Aquilaria species which belong to the family of Thymelaeaceae. The long period of agarwood formation in nature that takes many decades to develop had restrained the supply in the market which leads to overexploitation of gaharu in Aquilaria spp. in the forest. Thus, Aquilaria malaccensis has been listed in Appendix II of Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Fungi were used to induced agarwood in Aquilaria trees. Agarwood is formed due to interaction between fungi and plant defense mechanism. Depletion of wild resource from the jungle leads to the high price of agarwood. Hence, it is the main concern to be handled by the researchers to find alternative ways to induce gaharu formation to meet the global demand for agarwood trading. Therefore, agarwood needs to be artificially induced for a better amount of resin production. This research was conducted to formulate microbial consortia that made up of fungi as fungal inoculants for agarwood induction in Aquilaria spp.. The effectiveness of the formulated microbial consortia was observed based on the colour and mean length of infected zone formation after a three month and six month inoculation periods in each wet and dry seasons, respectively. Aquilaria spp. was inoculated with three types of formulated fungal inoculants which were Formulation 1 (F1) consisting combination of Trichoderma sp. and Aspergillus sp., Formulation 2 (F2) consisting combination of Fusarium sp. and Penicillium sp., whereas Formulation 3 (F3) consisting combination of Trichoderma sp., Lasiodiplodia sp. and Curvularia sp.. Negative control used in this study was sterile distilled water. In this study, iv the fungal inoculants were inoculated into the Aquilaria trees by using the bottle drip method. Production of secondary metabolites of induced Aquilaria trees was analysed by using Gas Chromatography-Mass Spectrometry (GC-MS). A total of 115 chemical compounds were detected in all inoculated trees where inoculation during the dry season produced a relatively greater number of chemical compounds compared to the wet season. Major constituents of the gaharu such as sesquiterpenes, chromones, fatty acid methyl ester, and aromatic compounds were found in inoculated Aquilaria trees. New agarwood sesquiterpenes, cryptomeridiol (0.93%) has been detected in F3 inoculated Aquilaria tree after six months inoculation during the dry season. Besides, aromatic compound such as 3’,5’ dimethoxyacetophenone (0.25%), guaia-1 (10), 11-diene (0.45%), octacosanol (0.57%) and heptadecanolide (0.24%) can only be detected in F3 inoculated Aquilaria trees. These chemical compounds were known as major constituents that contribute to aromatic properties in agarwood. The findings showed that F3 inoculant (a combination of Trichoderma sp., Lasiodiplodia sp., and Curvularia sp.) is the most potential fungal inoculant in inducing resin in Aquilaria tree due to its largest length of resinous zone and the presence of metabolic compound in inoculated Aquilaria trees after three and six months inoculations for both wet and dry seasons, respectively. From this study, it is recommended that the formulated microbial consortium can be used as potential agarwood fungal inoculant for future sustainable supply of agarwood.